Bridging regulation and practice: CJEU and Dutch case law on botanical health claims - Karin G. M. Lenssen; Karin G. M. Lenssen; Alie de Boer; Alie de Boer (Frontiers in Pharmacology)
IntroductionEven though botanicals are increasingly popular ingredients for food supplements, health claims related to their putative bene ts remain unclearly regulated.MethodsThrough an analysis of EU and national case law from the Netherlands, including self-regulatory decision-making, we have studied the implications of case law on botanical health claims.ResultsOur analysis reveals that there are multiple issues related to claims on botanical-containing products: whether it should be classi ed as food or medicine; what statements should be understood as health claims; what type of evidence should underlie health claims and, more specically, botanical health claims; and how to deal with online commercial communication. The case law analysis highlights rst that a gray area will continue to exist when classifying products as foods or medicinal products, particularly when it comes to products that contain botanical ingredients. Most importantly, our study also reveals that claims—even when they are on hold, like botanical claims—need a certain scienti c foundation before they can be used on products. Finally, the courts believe that even though on-hold claims will continue to give a certain level of uncertainty for food business operators, this is not a legal but rather a regulatory issue.DiscussionThe findings from our case law analysis highlight that even though case law is useful in further interpretation of legislation, it does not provide any policy advancement. In the case of botanicals, a political decision regarding their substantiation is highly desired.